Pengaruh Waktu Pengadukan Biosorben Cangkang Maggot dalam Menyisihkan Ion Fe - Nur Aini Maulidifa; Euis Nurul Hidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Heavy metals, including iron (Fe), are commonly found in industrial wastes and end up contaminating water sources. Although their presence is essential in various industrial applications, high concentrations of heavy metals can lead to toxicity and health problems. Therefore, adsorption methods have been used as an approach to reduce the concentration of heavy metals in water. Maggot shells have been identified as potential biosorbents because they contain chitin compounds that can interact with heavy metals. The aim of this study was to evaluate the influence of stirring time on the adsorption process of maggot shells on the heavy metal Fe. The adsorption method used was a batch system with a stirring speed of 150 rpm. The results showed that the increase in adsorption efficiency was consistent with the increase in stirring time. Stirring time plays a crucial role in enhancing the interaction between the biosorbent and Fe metal ions, resulting in increased removal efficiency. However, the effect of stirring time is limited after the saturation point is reached.